Behavior of Hospital Mid-Level Managers in Budgeting Implementation - an Empirical Study - Cygańska, Małgorzata; Marcinkiewicz, Zbigniew (Olsztyn Economic Journal, 2014)
This study examines the introduction of management changes in a hospital based on the Lewin’s model. It focuses on the attitudes of a hospital’s mid-level managers to a new management-budgeting system. The conclusions are based on empirical research. The article analyzes the change implementation process related to the budgeting system in a hospital with particular consideration of the attitudes and the level of involvement of employees in the performance of new tasks. The analysis showed that the top management of hospitals and the mid-level management do not see the effects of changes related to budgeting in similar ways. This may cause significant hindrances to the process of employees adopting attitudes and behaviors required by the top management. The diversity of opinions in this area may result from: not specifying in detail the targets of budgeting by the top management or not informing the medium-level management of them, a lack of set measures for evaluation of the performance of budget tasks, aiming at achievement of the assumed targets by means of methods not accepted by the employees.